The SS Method to Obtain an Optimal Solution of Transportation Problem - Rahmasari, Shafira Meiria; Susilawati; Ida Hamidah (EDUPEDIA Publisher, 2023)
The transportation problem is a problem of distributing goods from several sources to several destinations so as to minimize transportation costs. Solving the transportation problem is needed to determine how many items must be sent from each source to each destination that must be met with minimum shipping costs. The purpose of this research is to examine, investigate, and apply the SS method to the minimum case transportation problem, both balanced and unbalanced. This research method is in the form of literature study and literature review from various sources that are relevant to the research. The results showed that the SS (Sheethalakshmy Srinivasan) method proposed by A. Seethalakshmy and Dr. N. Srinivasan can provide the optimal solution without having to find an initial feasible solution to the transportation problem so as to reduce the calculation time. This method provides an optimal solution for the minimum case transport problem for both balanced and unbalanced cases.